PHOTOBOOK DESIGN AS A MEDIA FOR INTRODUCTION OF TOURIST ATTRACTIONS ON SENGGARANG ISLAND” - Hendi Sama; Kevin Kevin (Universitas Internasional Batam, 2022)
Senggarang Island is a small village in the city of Tanjung Pinang which is inhabited by residents with a majority ethnic Chinese. Senggarang is known as a place where the gods gather. On this island there are various tourist objects, such as temples, and statues that are unique and have their own charm. However, there are still many people who do not know the beauty of natural tourism on Senggarang Island. The purpose of this study is to promote and introduce several tourist attractions on Senggarang Island by using photobooks as an introduction medium. This photobook contains a collection of information about tourist attractions such as a description of the place, the facilities available, and the atmosphere around Senggarang Island. In the process of designing the photobook, the application used by the author is Adobe Lightroom to edit photos and Adobe Photoshop CC 2018 to design the photobook. Data collection methods used in this activity are observation, image documentation, and interviews. The result of the implementation of this research is a printed photobook with a size of 20x20cm which contains an introduction to Senggarang Island. With the design of this photobook, it is hoped that it can increase visitors and increase public knowledge about Senggarang Island.